Impact of stocking densities and road transport distances on meat quality and malondialdehyde levels in semitendinosus and infraspinatus muscles of Brahman crossbred heifers in a tropical climate - Abubakar, Ahmed A.; Idrus, Zulkkifli; Goh, Yong M.; Kaka, Ubedullah; Sabow, Azad B.; Imlan, Jurhamid C.; Othman, Azalea H.; Raghazali, Razlina; Sazili, Awis Q. (Informa UK Limited, 2024)
Transporting cattle in tropical climates substantially impacts oxidative stability and meat quality due to increased stress levels. The objective of this research is to assess the impacts of road transport with two different distances and three stocking densities on meat quality indices and malondialdehyde (MDA) levels in the infraspinatus (IF) and semitendinosus muscles of Brahman crossbred heifers in a tropical climate. Sixty Brahman crossbred heifers were exposed to two different road travel distances: 450 and 850 km. Each travel distance was divided into three different stocking densities: low density of 200 kg/m2, medium density of 400 kg/m2 and high density of 600 kg/m2. The number of animals in each stocking density was kept equal. Following transit, IF and semitendinosus muscle samples were collected and assessed for meat quality characteristics, including colour attributes, pH, muscle glycogen contents, Warner-Bratzler shear force (WBSF), cooking loss and lipid oxidation. The findings showed notable impacts of livestock densities and road transport distances on meat quality parameters and MDA levels in Brahman crossbred heifers’ muscles. Similarly, increased livestock densities resulted in higher levels of MDA and alterations in meat quality measures than lower densities following both distances of road transportation. These findings highlight the significance of optimising livestock density and reducing road transport lengths to maintain the oxidative stability of meat quality in heifers.